Determination of maximum neutral point current injection limits in a three-phase neutral-point-clamped converter - Jiang, Zhuolin (Nanyang Technological University, 2020)
The neutral-point-clamped (NPC) converter is nowadays widely used in the industry. The main features of the NPC converter are: (1) The high quality ac voltages that the converter can produce thanks to its capability to generate three voltage levels at its outputs, and (2) its ability to deal with higher operating voltages than the classical two-level converters. These features make the NPC converter very suitable for high power applications. Many applications employing NPC converter require an average neutral point (NP) current injection in certain operating conditions such as bipolar dc-bus, back-to-back NPC converter and power compensator, etc. However, in these applications if the average NP current is not properly compensated over one fundamental period, the nonzero average current flows into the NP and in turn, the capacitors, which breaks the balanced condition of the bipolar dc-buses. To tackle this problem, an average NP current is required to be injected into the NP and compensate the excessive average NP current accordingly. In order to better implement the average NP current injection, it is necessary to envision the maximum and minimum average NP current that can be injected with NPC converter. For the proposed calculation, a three-level modulation technique is employed in which one of the three phases is selected to switch between positive dc-rail and negative dc-rail while the rest of the two phases switch into consecutive levels. In addition, to further determine the average NP current injection limits, the NPC converter switching two phases in three voltage levels is also analyzed in this thesis. The maximum and minimum average NP current injection limits are calculated considering different loading conditions. The negative sequence of currents and harmonic components are superimposed to the positive sequence of currents and the influences of linear imbalances and harmonics on the average NP current injection limits are described. It is found that with the addition of a negative sequence of currents (linear imbalance), the maximum and minimum average NP current injection limits remain symmetrical and increase with higher amount of the negative sequence of currents added. The addition of the odd-order current harmonics from a nonlinear load keeps the average NP current injection limits balanced, while the even-order harmonics can cause the NP current injection limits asymmetrical. Index Terms—Neutral-point current, linear imbalances, nonlinear loads, three-level modulation, neutral-point-clamped (NPC) converter.